A Novel UPLC Method Development and Validation of Mirabegron Determination in Pharmaceutical Dosage Forms - Anupama, B.; Viswanath, A.; Azizunnisa, .; Vaseemunnisa, Md. (Novel Aspects on Pharmaceutical Research Vol. 2, 2023)
The main aim of this investigation is to develop an accurate, simple and fast Ultra-Performance Liquid Chromatography (UPLC) method for the determination of Mirabegron in pharmaceutical dosage forms Mirabegron is a drug that eases the symptoms of overactive bladder. Mirabegron activates the \(β\)3 adrenergic receptor in the bladder's detrusor muscle, causing muscular relaxation and bladder capacity expansion. There have been a few measurement techniques found, however they are cumbersome and time consuming. The amount of Mirabegron in pharmaceutical dosage forms was determined using a simple, exact, precise and useful UPLC technique that was established in the current study. On Acquity BEH C18 (50*3.0mm. 1.7m), chromatographic separation was achieved by the isocratic elution mode using mobile phase containing Potassium di hydrogen phosphate: Methanol (70:30) v/v with a UV detection wavelength of 254 nm. Validation of the developed UPLC method was done as per the guidelines of the International Conference on Harmonization in terms of system suitability, precision, accuracy, specificity, sensitivity, linearity, and robustness.